Understanding, Experience, and Response Strategies to Sexual Harassment Among Chinese College Students - Li, Xiaomin (Journal of interpersonal violence, 2023)
Sexual harassment is a serious problem, and with a growing population of college students in China, the phenomenon is becoming prevalent. Using the 2010 data from the Third Survey on Chinese Women’s Social Status, we examined relationships between understanding of sexual harassment and experience/response among Chinese college students. The results show that college students understand physical sexual harassment better (88%; unwanted sexual requests: 92%) than verbal and visual sexual harassment (54% and 70%, respectively). Understanding is higher among females than males, with a margin between eight to 21%. At a prevalence of 30%, the experience of verbal sexual harassment is the highest compared to other forms of harassment. Males were more likely to experience verbal and visual sexual harassment, while females were more likely to experience physical sexual harassment. In any event of sexual harassment, expressing dissatisfaction and stopping it is the response strategy that most resonates with respondents. It varied between 62% and 70% across forms of sexual harassment. Reporting to teachers or school authorities resonates least, varying between 0.30% and 2.28%. Understanding sexual harassment was strongly associated with a reduced likelihood of harassment. The equivalent odds ratios varied between 0.41 and 0.33 (p < .001), or 59–67% reduced likelihood across the forms of sexual harassment. Understanding sexual harassment was also strongly associated with an increased likelihood of not reacting passively or staying silent. Odds ratio varied between 1.99 and 3.86 (p < .001), about a minimum of twofold increased likelihood. Parents should strive to involve in their children’s sex and sexual rights education, particularly during adolescence, to help them inculcate values against sexual harassment. Also, colleges and universities can bolster their curriculum with elective courses on sex education and regularly organize symposiums on sexual harassment to create a better understanding and awareness among students.